Hutan pasca pemanenan: melindungi satwa liar dalam kegiatan hutan produksi di Kalimantan - Meijaard, E.; Sheil, Douglas; Nasi, Robert; Augeri, D.; Rosenbaum, B.; Iskandar, D.; Setyawati, T.; Lammertink, A.; Rachmatika, I.; Wong, A.; Soehartono, T.; Stanley, S.; et al. (Center for International Forestry Research, 2006)
This book presents a technical review of ecological and life history information on a range of Bornean wildlife species, aimed at identifying what makes these species sensitive to timber harvesting practices and associated impacts. It addresses three audiences: 1) those involved in assessing and regulating timber harvesting activities in Southeast Asia, 2) those involved in trying to achieve conservation goals in the region, and 3) those undertaking research to improve multipurpose forest management. This book shows that forest management can be improved in many simple ways to allow timber extraction and wildlife conservation to be more compatible than under current practices. The recommendations can also be valuable to the many governmental and non-governmental organisations promoting sustainable forest management and eco-labelling. Finally, it identifies a number of shortcomings and gaps in knowledge, which the hope can interest the scientific community and promote further research. This review is, an important scientific step toward understanding and improving sustainable forestry practices for long-term biodiversity conservation. Even in the short term, however, significant improvements can be made to improve both conservation and the efficiency of forest management, and there is no need to delay action due to a perceived lack of information. In the longer term it is expected that the recommendations from this review will be implemented, and that further research will continue to help foster an acceptable balance among the choices needed to maintain healthy wildlife populations and biodiversity in a productive forest estate.